Imperialism and Disorder: The Global Ambitions and Internal Decay of the United States - Wood, Geoffrey (Labour / Le Travail, 2005)
The article reviews and comments on "Incoherent Empire" by Michael Mann, "Contours of Descent: US Economic Fractures and the Landscape of Global Austerity" by Robert Pollin, and "Tyranny in America: Capitalism and National Decay" by Neal Wood.